Genetic variation and structure of endemic and endangered wild celery (Kelussia odoratissima Mozaff.) quantified using novel microsatellite markers developed by next-generation sequencing - Mahdavikia, Faezeh; Ebadi, Mohammad-Taghi; Shojaeiyan, Abdolali; Ayyari, Mahdi; Falahati-Anbaran, Mohsen (Frontiers in Plant Science, 2024)
Kelussia odoratissima Mozaff. (Apiaceae) is a native plant that has been traditionally consumed in Iran’s food and pharmaceutical industries. Overharvesting of the taxon, especially at the beginning of the growing season, due to its considerable medicinal and economic value, is believed to be the main reason for the extirpating of this plant. The consequences of the severe anthropogenic impacts on the genetic diversity of populations are poorly known. In order to investigate the level of genetic variation and patterns of the genetic structure of K. odoratissima, we developed novel microsatellite markers using the 454 Roche next-generation sequencing (NGS) platform for the first time. Out of 1,165 microsatellite markers bioinformatically confirmed, twenty-five were tested, of which 23 were used to screen genetic variation across 12 natural populations. Our results showed that the average number of alleles per locus and the polymorphic information content (PIC) were 10.87 (range 7 to 27), and 0.81 (range 0.67 to 0.94), respectively. The mean observed and expected heterozygosities (± SD) across all populations were 0.80 ± 0.31 and 0.72 ± 0.14, respectively. The average pairwise FST among the populations was 0.37 (range 0.04 to 0.81). Bayesian and distance-based clustering, and principal coordinate analyses revealed at least four major genetic clusters. Although high level of structure can be explained by landscape topography and geographic distance, presence of admixed populations can be associated to seed or pollen dispersal. Contrary to expectations, the high level of genetic variation and lack of inbreeding suggest that overexploitation has not yet significantly purged the allelic variability within the natural populations in protected areas.